Effects of Turkish propolis and silver sulfadiazine on burn wound healing in rats - Han, MC; Durmus, AS; Karabulut, E; Yaman, I (Ecole Nationale Veterinaire Toulouse, 2005)
This experiment was conducted to compare 50 % propolis cream and silver sulfadiazine (SSD) for healing of burned wounds in rats. Sixty male Wistar albino rats' were divided into three equal groups. A burned model was constituted on the back of all rats. The burned areas in the first. second and third groups were covered daily with 50 % propolis. SSD skin cream and cold cream (control) respectively. Ten and 21 days later the rats were anaesthetized and the burned skin tissue samples were collected front rats for histopathological examinations. In conclusion, application of 50 % propolis cream is significantly effective in healing of burned skin wounds in rat model.
Keywords: propolis; silver sulfadiazine; burn; rat